Modeling the figure in clay a sculptor's guide to anatomy - Lucchesi, Bruno (New York Watson-Guptill, 2010)
For thirty years, Modeling the Figure in Clay has been an indispensable anatomical resource for people who think, see, and understand form best in the round: sculptors.

In the thirtieth anniversary edition of this classic work, master sculptor Bruno Lucchesi invites you on a guided tour of the human form. Follow him as he creates a figure in clay—literally from the inside out—starting with the skeleton, laying on the muscles to show male and female anatomy, and finishing with a complete figure sculpture with every detail of face and hair carefully modeled.
Keywords: Figure sculpture -- Technique; Modeling; Human figure in art